Statistics and Variability of Darbandikhan and Dukan dam Inflow time series - Mustafa, Nawbahar F. (Sulaimani Journal for Pure and Applied Sciences, 2017)
Flow, low flow statistics, and variability of Darbandikhan and Dukan inflow time series have been analyzed. Darbandikhan and Dukan dams’ inflow time series were best fitted with three parameter inverse Gaussian distribution. Long term, annual, and monthly flow duration curves (FDCs) are constructed. Two parameters logarithmic function appeared to be the most appropriate functions fitted to FDCs. Low flow percentiles are extracted from flow duration curves for 95, 90, 75, 70, 50, and 25 percentiles. Annual minimum 1-, 3-, 7-, 14-, 30-, 60-, and 90-day mean inflow with recurrence intervals of 2, 5, 10, 20, 30, and 50 years were estimated. Base flows were separated from long-term inflow time series. Results indicated that a large amount of long-term inflow was supported by base flow for both Darbandikhan and Dukan dams’ inflow time series. The discharges were generally less than their mean inflow with no large fluctuations. The trend of monthly mean inflow discharge versus time have been analyzed using different methods. Results are indicating a signiﬁcant negative monthly trends of 0.488 m3/s and 0.593 m3/s with reduction percentages of 0.0127 % and 0.0120% for Darbandikhan and Dukan dams’ inflow time series; respectively. The results of current study were compared with USGS Data Series 540 results. All month’s inflow defined a reduction that maximized in August. Comparison of low flow statistics are also referred to maximum reduction percentage in Q95% which is occurring commonly in summer. The larger reduction during summer months is indicating artificial water withdrawals from feeding streams of the dams during periods of no rain.
Keywords: Low flow; Flow duration curve; Trend; Darbandikhan dam; Dukan dam